Between the Social and the Personal: Israeli Male Gay Parents, Surrogacy and Socio-Political Concepts of Parenthood and Gender. Issue 1 (1st January 2019) - Tsfati, Maya; Ben-Ari, Adital
ABSTRACT: This work focuses on the effects of dominant concepts of parenthood and gender on gay men who became parents through surrogacy. Based on the analysis of 39 in-depth, semistructured interviews with gay fathers, we show that gay fathers' parenting experiences are shaped by the heteronormative discourse on parenthood, yet they resist its gendered attributes. Gay parenthood is revealed as confronting the social concepts on parenthood, in particular on motherhood, and their socio-political meanings. The tension between the social concepts and the participants' perceptionsy leads them to confront their social environment and to construct alternative discourse to the social discourse of parenthood and gender, suggesting that gay parenthood subverts under existing concepts of parenthood, gender and their meanings within the state.